2020
DOI: 10.1038/s41566-020-00701-x
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Mie driven random quasi-phase-matching

Abstract: High-quality crystals without inversion symmetry are the conventional platform to achieve optical frequency conversion via three wave-mixing. In bulk crystals, efficient wave-mixing relies on phase-matching configurations, while at the micro-and nanoscale it requires resonant mechanisms that enhance the nonlinear light-matter interaction. These strategies commonly result in wavelength-specific performances and narrowband applications. Disordered photonic materials, made up of a random assembly of optical nonli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 49 publications
(67 reference statements)
2
44
0
Order By: Relevance
“…A separate major direction is associated with the use of mesoscale particles in microscopy [38,39,106,172]. In the authors' opinion, the creation of mesoparticle chains with the required properties using the phase-matching mechanism that relies on the coupling of random quasi-phase-matching with the Mie resonance of the entirely disordered mesostructure is promising [173]. The generation of hot spots, having giant values of the local wavenumber vectors, by use a superoscillation effects [9,10] is extremely promising not only for mesoscale photonics and superresolution imaging, but also for diffractive optics [174], whose research was begun back in 1990 [175].…”
Section: Discussionmentioning
confidence: 99%
“…A separate major direction is associated with the use of mesoscale particles in microscopy [38,39,106,172]. In the authors' opinion, the creation of mesoparticle chains with the required properties using the phase-matching mechanism that relies on the coupling of random quasi-phase-matching with the Mie resonance of the entirely disordered mesostructure is promising [173]. The generation of hot spots, having giant values of the local wavenumber vectors, by use a superoscillation effects [9,10] is extremely promising not only for mesoscale photonics and superresolution imaging, but also for diffractive optics [174], whose research was begun back in 1990 [175].…”
Section: Discussionmentioning
confidence: 99%
“…[ 144,145 ] New studies have emerged in this area in recent years and revealed that these activated processes in BaTiO 3 and LiNbO 3 nanoparticles are produced through solvothermal processes. [ 146–149 ] For instance, an increase in the size of BaTiO 3 nanoparticles shifted the SHG peak to the red portion (600 nm) due to the influence of the MD mode, whereas LiNbO 3 was demonstrated to operate in the near‐UV region. More materials can be used to explore suitable candidates that feature peculiar optical properties and cover the far‐red and IR region.…”
Section: Manipulation Of the Scattering Characteristicsmentioning
confidence: 99%
“…developed 3D disordered microspheres by bottom‐up assembly of BaTiO 3 nanocrystals and demonstrated broadband and simultaneously Mie‐enhanced SHG within a 100 nm wavelength range. [ 149 ]…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…Second harmonic generation (SHG) from nanostructures is at the heart of metamaterials and nanooptics since it does not strictly require the macroscale phase-matching condition [1,2]. Especially, the miniaturization and integration trends of metamaterials make it possible to engineer and utilize SHG in many applications, such as characterizations of structural properties and laser beam [1].…”
Section: Introductionmentioning
confidence: 99%